Association between circulating miRNAs and spinal involvement in patients with axial spondyloarthritis - Prajzlerová, Klára; Grobelná, Kristýna; Hušáková, Markéta; Forejtová, Šárka; Jüngel, Astrid; Gay, Steffen; Vencovský, Jiří; Pavelka, Karel; Šenolt, Ladislav; Filková, Mária (PloS one, 2017)
OBJECTIVES: Dysregulation of miRNAs and their target genes contributes to the pathophysiology of autoimmune diseases. Circulating miRNAs may serve as diagnostic/prognostic biomarkers. We aimed to investigate the association between circulating miRNAs, disease activity and spinal involvement in patients with axial spondyloarthritis (AxSpA). METHODS: Total RNA was isolated from the plasma of patients with non-radiographic (nr)AxSpA, patients with ankylosing spondylitis (AS) and healthy controls (HC) via phenol-chloroform extraction. A total of 760 miRNAs were analysed with TaqMan® Low Density Arrays, and the expression of 21 miRNAs was assessed using single assays. RESULTS: Comprehensive analysis demonstrated the differential expression of miRNAs among patients with progressive spinal disease. Of the 21 miRNAs selected according to their expression patterns, the levels of miR-625-3p were significantly different between nr-AxSpA patients and HCs. We found no correlation between miRNA levels and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) in nr-AxSpA patients. Selected miRNAs, such as miR-29a-3p, miR-146a-5p or miR-222-3p with an established role in extracellular matrix formation and inflammation were associated with spinal changes and/or disease activity assessed by BASDAI in AS patients, including miR-625-3p reflecting disease activity in AS with spinal involvement. CONCLUSIONS: Our data indicate that circulating miRNAs play a role in the pathogenesis of AxSpA and are also suggestive of their potential as biomarkers of disease progression. We hypothesize that differential systemic levels of miRNA expression reflect miRNA dysregulation at sites of spinal inflammation or bone formation where these molecules contribute to the development of pathophysiological features typical of AxSpA.
Keywords: dospělí; Spondylitis, Ankylosing; Female; biologické markery; C-Reactive Protein; Biomarkers; nemoci páteře; Adult; mladý dospělý; ženské pohlaví; ankylózující spondylitida; shluková analýza; lidé; Spondylarthritis; stanovení celkové genové exprese; stupeň závažnosti nemoci; Spinal Diseases; Male; progrese nemoci; Aged; Disease Progression; Young Adult; mikro RNA; MicroRNAs; lidé středního věku; C-reaktivní protein; senioři; mužské pohlaví; Severity of Illness Index; Cluster Analysis; Middle Aged; Gene Expression Profiling; spondylartritida; Humans